(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
The most commonly diagnosed arthritis is Knee Osteoarthritis. The main possible causes of Knee Osteoarthritis can be trauma, overweight, old age, lifestyle, calcium deficiency etc. In modern medicine, the available treatment for osteoarthritis is NSAIDS, Ca supplements, and at last, joint replacement. The present case study is about knee osteoarthritis which is caused due to trauma. Panchakarma (Snehana, Swedana, Janu Basti, Matra Basti) has a significant role in the management of Osteoarthritis. So, here’s an attempt to show its efficacy, along with oral Ayurvedic medications, which will be helpful for further studies.